IMPLEMENTASI PKPU 23, 28 DAN 33 TAHUN 2018 TENTANG PEMASANGAN ALAT PERAGA KAMPANYE DI KABUPATEN HULU SUNGAI UTARA - Arsyad, Muhamad (PPPM STIA Amuntai, 2019)
The problems faced by the Hulu Sungai Utara Regency General Election Commission (KPU) problems in terms of the implementation of the General Election Commission's (APK) Campaign Props only allow for the installation of a maximum of 5 (five) billboards, limitation of the location of billboards and APK Designs. not in accordance with the provisions made by the Candidate. The purpose of this study was to identify and analyze the implementation of PKPU 23, 28 and 33 of 2018 regarding the installation of campaign props in the Hulu Sungai Utara Regency and the factors that hindered the implementation. The research method is qualitative descriptive, type and source of data, namely primary data through observation, interviews while secondary data through data that is on the General Election Commission and related services in Hulu Sungai Utara Regency, the technique used in sampling is the purposive sampling technique is withdrawal of samples in purpose or can be determined in accordance with the requirements (characteristics, characteristics, characteristics, criteria). The results of the study show that in the Implementation of PKPU 23, 28 and 33 regarding the installation of Campaign Teaching Devices in the Upper Sungai Utara District it has been going well, where one indicator is the coordination that is always carried out by election organizers, communicating all related matters Terms of installation of Campaign Teaching Devices. This is evidenced by the lack of cases of alleged violations which were only 29 cases. And the factors that influence are factors of Communication, Human Resources, Attitudes and Bureaucracy. The suggestions given for input include the need for socialization, the implementers of election oversight in the field must also understand the rules correctly, and the authors hope that election organizers, both KPU and Bawaslu, have the same understanding of PKPU's provisions on campaign props.